2014
DOI: 10.1371/journal.pone.0090661
|View full text |Cite
|
Sign up to set email alerts
|

Two Kinds of Ferritin Protect Ixodid Ticks from Iron Overload and Consequent Oxidative Stress

Abstract: Ticks are obligate hematophagous parasites that have successfully developed counteractive means against their hosts' immune and hemostatic mechanisms, but their ability to cope with potentially toxic molecules in the blood remains unclear. Iron is important in various physiological processes but can be toxic to living cells when in excess. We previously reported that the hard tick Haemaphysalis longicornis has an intracellular (HlFER1) and a secretory (HlFER2) ferritin, and both are crucial in successful blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…In addition to the role of storage in mammals, insect ferritins have shown to assist in iron transport (Pham and Winzerling, 2010). Ferritin has been previously identified in several tick species including Ornithodoros moubata , Ixodes ricinus , H. longicornis and R. microplus (Galay et al, 2014; Hajdusek et al, 2010; Kopáček et al, 2003). Silencing of ferritin has demonstrated negative effects on tick feeding and tick reproduction (Galay et al, 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the role of storage in mammals, insect ferritins have shown to assist in iron transport (Pham and Winzerling, 2010). Ferritin has been previously identified in several tick species including Ornithodoros moubata , Ixodes ricinus , H. longicornis and R. microplus (Galay et al, 2014; Hajdusek et al, 2010; Kopáček et al, 2003). Silencing of ferritin has demonstrated negative effects on tick feeding and tick reproduction (Galay et al, 2013, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Ferritin has been previously identified in several tick species including Ornithodoros moubata , Ixodes ricinus , H. longicornis and R. microplus (Galay et al, 2014; Hajdusek et al, 2010; Kopáček et al, 2003). Silencing of ferritin has demonstrated negative effects on tick feeding and tick reproduction (Galay et al, 2013, 2014). Immunization trials against ferritin where tick infestations were reduced indicate that tick ferritins are essential for successful feeding (Hajdusek et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…RNAi is a good technique for screening candidate antigens for vaccine development [12]. Our previous gene silencing studies showed that HlFERs are crucial to the blood feeding and reproduction of H. longicornis [17], providing protection against ironmediated oxidative stress [18] and making them good candidate vaccine antigens. Our vaccination experiments showed that both rHlFER1 and rHlFER2 are highly immunogenic, inducing host antibody production.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies on two ferritins of the hard tick H. longicornis using RNAi showed that both are physiologically important in blood feeding and reproduction [17] by preventing iron overload and the occurrence of oxidative stress [18]. Furthermore, a previous study showed that FER2 vaccination had considerable effects on infestation of I. ricinus and R. microplus [19].…”
Section: Discussionmentioning
confidence: 99%
“…Silencing two types of the iron storage protein ferritin greatly reduced the ticks' capacity to engorge and produce eggs, also affecting post-blood meal survival due to occurrence of iron-mediated oxidative stress [113]. An iron regulatory protein responsible for translation of iron binding proteins was characterized in I. scapularis, with its knockdown greatly reducing egg hatchability [111].…”
Section: Genes Related To Structural and Metabolic Functionsmentioning
confidence: 99%